SIMULATION-BASED CONDUCTOR OPTIMIZATION FOR POWER DISTRIBUTION FEEDERS, A COMPARATIVE STUDY USING ETAP - Abdul Aziz; Zaheer Farooq; Hassan Zahid; Javed Khan Marwat; Aftab Zaman Awan; Romaisa Shamshad Khan; Muhammad Hussnain; Ali Mujtaba Durrani; Basit Ahmad (Spectrum of Engineering Sciences, 2025)
The electrical distribution system is the final and most crucial stage in the power grid, responsible for delivering electric power to consumers. As distribution networks are located close to end users, it becomes essential to thoroughly plan and manage the system to minimize power losses and ensure that voltage levels remain within acceptable limits for reliable operation. A significant aspect of such planning involves selecting the optimal conductors for each section of the distribution feeder, as the choice of conductor directly influences the system's efficiency and performance. This paper focuses on the practical planning of a distribution system by selecting the optimal conductors for an 11 kV distribution feeder, aiming to minimize power losses and enhance voltage levels. A novel approach is proposed for optimal conductor selection in radial distribution networks, utilizing power flow studies in the Electrical Transient Analyzer Program (ETAP). The methodology involves comparing the results of different conductor configurations while considering the increasing load demands over time. Several objective functions are incorporated into the model, such as maintaining voltage limits, ensuring adequate current-carrying capacity, selecting the appropriate conductor sizes and types, minimizing power loss costs, and improving the overall voltage profile. The findings demonstrate that reducing energy losses within the distribution system conserves available system capacity, eliminating the need for additional capacity installation. This approach also yields improved system stability, a more optimal voltage profile, and a decrease in both active and reactive power losses. Furthermore, the system’s energy handling capacity is enhanced while maintaining minimal costs. This method offers a comprehensive solution for optimizing the distribution system, ensuring improved performance and efficiency while minimizing operational costs and enhancing the system’s overall reliability.